AN EVALUATION ON OUTCOME OF OIL PALM REPLANTING SCHEME (TSSPK) AND NEW PLANTING SCHEME (TBSPK) - Sheilyza Mohd Ishak; Zaki Aman; Humaira Mat Taib, (INTERNATIONAL JOURNAL OF MODERN TRENDS IN SOCIAL SCIENCES (IJMTSS), 2024)
The Oil Palm Assistance Scheme for Replanting (TSSPK) and the New Planting (TBSPK) for Independent Smallholders (ISH) were inaugurated in 2011 as part of the 10th Malaysia Plan. It is a subset of the National Key Economic Area (NKEA) Oil Palm Commodities Entry Point Project 1 (EPP1). Among the assistance included in these schemes are the high-quality seedlings, agricultural inputs such as fertilisers and pesticides along with the cash fund for land preparation and cultivation of the seedlings. The smallholders who participated in these schemes were also given extension services by the MPOB extension agent (TUNAS) on various aspects of oil palm management. A total of 382 participants were involved and responded to the survey. The proportion of respondents are from Sabah (38.5%), Sarawak (38%), and Johor (23.6%). The study found that the average age of the participants mostly is 60 years old and above (40.1%), and 57.4% of participants were the owner of the oil palm plantation. The range of fresh fruit bunch (FFB) production harvested for the first and second year is between 0 - 4.6t/ha/year, which is slightly low due to the El Nino occurrence in 2016. A profit in income was recorded from the FFB sales after participating in the scheme. The low-income category recorded a decrease of 30.11% while the higher income category showed an increased between 2.66% to 16.59% after they joined the schemes. Some participants also implemented the integrated cash crops alongside the oil palm to generate income while waiting for the immature oil palm to produce yield. This study shows that most of the respondents complied with the Good Agriculture Practice (GAP) after joining the scheme. Most of the participants were pleased with the implementation of the schemes and services done by the TUNAS Officers and gave them an excellent rating. Several improvements are suggested such as agriculture input distribution, clustering the smallholders into cooperatives, continuity of GAP implementation, and comprehensive research in the future.